Disentangling the Advective Brewer‐Dobson Circulation Change - P. Šácha; R. Zajíček; A. Kuchař; R. Eichinger; P. Pišoft; H. E. Rieder (Geophysical Research Letters)
Abstract Climate models robustly project acceleration of the Brewer‐Dobson circulation (BDC) in response to climate change. However, the BDC trends simulated by comprehensive models are poorly constrained by observations, which cannot even determine the sign of potential trends. Additionally, the changing structure of the troposphere and stratosphere has received increasing attention in recent years. The extent to which vertical shifts of the circulation are driving the acceleration is under debate. In this study, we present a novel method that enables the attribution of advective BDC changes to structural changes of the circulation and of the stratosphere itself. Using this method allows studying the advective BDC trends in unprecedented detail and sheds new light into discrepancies between different data sets (reanalyses and models) at the tropopause and in the lower stratosphere. Our findings provide insights into the reliability of model projections of BDC changes and offer new possibilities for observational constraints.